(untitled) (Applied Biological Research, 2013)
The present study conducted at the Institute Farm of National Research Centre on Pig, Guwahati (Assam) was aimed to assess the pre-weaning growth pattern and construct growth band in ‘Ghungroo’ and ‘Niang Megha’ pigs maintained under standard breeding, feeding and management conditions. Piglets of both breeds were maintained under similar management conditions with creep feed costing Rs. 15.76 kg-1amounting to Rs. 46.35 upto weaning age (56 days). The overall mean weight at birth and weaning was 0.96±0.02 and 7.07±0.26 kg, respectively, for ‘Ghungroo’ pig and 0.64±0.02 and 5.47±0.13 kg, respectively, for ‘Niang Megha’ pig. The growth curves were linear for all the cases with accuracy of prediction ranging between 97.6 and 99.5%. Breeds of animal showed highly significant difference in body weight for all the weeks. The growth band developed can be used for early selection of animals.